Energy Flow through Summer Cropping In a Mountain Agro-Ecosystem in Kumaun Himalaya - Rastogi, Akanksha; Singh, Kundan; Singh, Vir; Arunachalam, A. (Indian Journal of Hill Farming, 2018)
Energy flow through a mountain agro-ecosystem was analysed in a cluster of five mid-altitude villages in the Pithoragarh district of the Kumaun Himalaya during summer (Kharif) cropping in 2007. Information was derived from 50 families (10 families in each village), resource persons and secondary sources. There were, on an average, 87 households per village. The average family size of the villages was 6.22. Average population per village was 476. Anaverage land holding size was one ha. Upland rice and finger millet-pulses covered the largest area. On an average, there were 64 bullocks, 46 cows, 98 buffaloes, and 144 goats per village.Maximum amount of energy (274.50x105 kJha-1) was invested through manure (53.55 percent of the total energy), followed by chemical fertilizers (97.09 x105 kJha-1) and pesticides (82.88 x105 kJha-1), and minimum through seeds (15.15x105 kJha-1). In the form of useful outputs (grain and straw), a gross energy value of 10260.95 x105kJha-1 was harvested during summer cropping. The largest amount of energy was produced through fruit production (3246.60x105kJha-1), which was about 32 percent of the gross energy produced in one ha cropland during summer season. Gross energy output - input ratio of the tree-based fruit crops was the highest (61.291) of all the crops. Root and tuber crops showedcomparatively higher energetic efficiency (17.833) than other vegetables (9.471). Amongst the food grain crops the maximum energetic efficiency (37.782) was recorded in amaranthkidneybean cultivation followed by finger millet-pulses (23.884) and the minimum in soybean cultivation (3.438).